2008
DOI: 10.1080/07317110802468546
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Caregivers' Most Pressing Concerns

Abstract: This primary-care-based study was designed to determine needs as identified by the informal caregiver. A total of 165 caregivers identified selected topics of concern. Depressed caregivers requested more information about depression, adult day care, grief, caregiver feelings, and relaxation. Caregivers of individuals with mild dementia requested more information on confusion, driving, patient depression, shadowing, telling the patient and others, grief, and depression. Behavioral (activities, combativeness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…CG + patients 2009/ UK [64]Selwood et al113 informal CGs; 67.9% female; 33.9% spouse; mean age = 61.2Self-administeredStrategies to reduce abusive behaviorList of 14 strategies which had either helped them already or that they thought would have the potential to help them avoid the abusive behaviors. Rating of the most helpful and the second most helpful strategies.yesNo, instrument developed for the studyCG 2008/ USA [65]Nichols et al165 informal CGs; 78.4% female; 50.3% spouse; mean age = 64.7 yearsSelection of a topic to discuss by CGBehavior, stress and coping pressing concerns25 pamphlets addressing particular behaviors and 12 pamphlets on CG stress/coping and improving the CG’s own well-being.yesNo, instrument developed for the studyCG 2010/ Netherlands [66]Peeters et al984 informal CGs; 71.6% female; 50.8% spouse; mean age = 62.8 yearsSelf-administeredProfessional support needs2 parts: 14 areas (30 items) on problems that are faced by persons with dementia and problems experienced by CGs; 56 items about the needs for additional professional support.yesNo, questionnaire developed for the studyCG 2010/Italy [17]Rosa et al112 informal CGs; 69% female; mean age = 55 years.Self-administeredCG’s needs“Questionnaire assessing the CGs’ needs”. Four areas (22 items): need of medical relevance, educational needs, need of emotional and psychological support, need of services.yesNo, questionnaire developed for the studyCG 2011 and 2016/ USA [24, 67]Koenig et alSteiner et al33 informal CGs; 29 female; 11 spouse; mean age = 62.2 yearsFace-to-face interviewsinformation needsList of 48 items: 25 items related to needing help for the care recipient +23 items related to needs of the CG.…”
Section: Resultsmentioning
confidence: 99%
“…CG + patients 2009/ UK [64]Selwood et al113 informal CGs; 67.9% female; 33.9% spouse; mean age = 61.2Self-administeredStrategies to reduce abusive behaviorList of 14 strategies which had either helped them already or that they thought would have the potential to help them avoid the abusive behaviors. Rating of the most helpful and the second most helpful strategies.yesNo, instrument developed for the studyCG 2008/ USA [65]Nichols et al165 informal CGs; 78.4% female; 50.3% spouse; mean age = 64.7 yearsSelection of a topic to discuss by CGBehavior, stress and coping pressing concerns25 pamphlets addressing particular behaviors and 12 pamphlets on CG stress/coping and improving the CG’s own well-being.yesNo, instrument developed for the studyCG 2010/ Netherlands [66]Peeters et al984 informal CGs; 71.6% female; 50.8% spouse; mean age = 62.8 yearsSelf-administeredProfessional support needs2 parts: 14 areas (30 items) on problems that are faced by persons with dementia and problems experienced by CGs; 56 items about the needs for additional professional support.yesNo, questionnaire developed for the studyCG 2010/Italy [17]Rosa et al112 informal CGs; 69% female; mean age = 55 years.Self-administeredCG’s needs“Questionnaire assessing the CGs’ needs”. Four areas (22 items): need of medical relevance, educational needs, need of emotional and psychological support, need of services.yesNo, questionnaire developed for the studyCG 2011 and 2016/ USA [24, 67]Koenig et alSteiner et al33 informal CGs; 29 female; 11 spouse; mean age = 62.2 yearsFace-to-face interviewsinformation needsList of 48 items: 25 items related to needing help for the care recipient +23 items related to needs of the CG.…”
Section: Resultsmentioning
confidence: 99%
“…This category was mentioned in most studies . One of the needs was the recruitment of competent help , requiring assistance in the verification of qualifications and references of people hired to help , and support in finding professional experts available for the needs of elderly and informal caregivers .…”
Section: Informal Caregivers' Needsmentioning
confidence: 99%
“…Nichols and associates (2009) surveyed caregivers (N = 165 total) and found that depressed caregivers (n = 56 of the 165 participants) requested more information about depression, adult day care, and caregiver's emotional feelings. In general, caregivers of individuals with mild dementia (n = 38 of the 165 participants) requested more information on topics like confusion, driving, and patient depression, in comparison to caregivers of individuals with advanced dementia (n = 122 of the 165 participants; Nichols et al, 2009).…”
Section: Introductionmentioning
confidence: 99%